Serotypes and antimicrobial resistance of Salmonella spp. isolated from patients with salmonellosis bacteremia in the Northern part of Thailand during 2003 – 2006 - Boonrat Vongchompoo; Sawalee Soasathan; Salakchit Chutipongvivate; Wanphen Thathong; Chuanpit Yungyin; Dech Phipatamornthipayawong (Journal of Associated Medical Sciences, 2008)
The study was conducted to determine the serotypes and antimicrobial resistance of Salmonella spp. isolates from patients with Salmonellosis bacteremia in the Northern part of Thailand during 2003 – 2006. Two hundred and fifty - four isolates of Salmonella spp. were classified into 22 serotypes using Gard Technique and Kauffmann-White antigenic scheme. Enteritidis was the most frequent serotype isolated (48.0%), following with Typhimurium (15.7%), Choleraesuis (14.2%) and others (22.0%), respectively. All isolates were tested for antimicrobial resistance to 10 different antimicrobial agents by the agar disk diffusion method. All isolates were susceptible to ciprofloxacin. They were highly resistant to nalidixic acid (54.3%), amplicillin (50.8%), tetracyclin (47.6%) and trimethoprim-sulphamethoxazole (33.5%). Choleraesuis serotype presented the highest rate of antimicrobial resistance serotype (97.2%) and multidrug ( > 3 agents) – resistance pattern (75.0%). Bull Chiang Mai Assoc Med Sci 2008; 41: 196-203.